Lead professor skills and classroom climate during online learning (LACCEI, 2024)
Virtual education in science and engineering careers brought with it great technological, psychological and pedagogical challenges, above all, for university professors. The professor's leadership took on great importance since he was the closest contact of the students with the university, everything that he planned, developed and evaluated was reflected in the climate of the virtual classroom. Therefore, the main objective of the research was to know how professor leadership contributed to the climate of the virtual classroom from the perspective of engineering students. The research was developed under the qualitative approach with a phenomenological design, the sample consisted of 21 engineering students with active enrollment in courses that were developed remotely in person in addition, the data was collected through interviews. According to the results, the professors showed transformational leadership skills that were valued positively by the students and, according to the testimonials, this had an impact on a positive experience in the classroom during the scheduled videoconferences. Finally, the students affirmed that these university learning experiences have contributed to their personal and professional development.